First microsatellite markers for Paspalum plicatulum (Poaceae) characterization and cross-amplification in different Paspalum species of the Plicatula group. - OLIVEIRA, F. A. de (2016)
Paspalum plicatulum is a perennial rhizomatous grass with natural diploid and polyploid cytotypes. It is a member of Plicatula, which has historically been recognized as a highly complex group containing species of ecological, ornamental and forage importance. The complex nature of the P. plicatulum genome makes it a challenging species for genetic research. This study aimed to develop and characterize microsatellite molecular markers in P. plicatulum and to evaluate their transferability to other Plicatula group species.